Achieving Ultrahigh Energy Density and Long Durability in a Flexible Rechargeable Quasi‐Solid‐State Zn–MnO2 Battery. Issue 26 (27th April 2017) - Zeng, Yinxiang; Zhang, Xiyue; Meng, Yue; Yu, Minghao; Yi, Jianan; Wu, Yiqiang; Lu, Xihong; Tong, Yexiang
Abstract : Advanced flexible batteries with high energy density and long cycle life are an important research target. Herein, the first paradigm of a high‐performance and stable flexible rechargeable quasi‐solid‐state Zn–MnO2 battery is constructed by engineering MnO2 electrodes and gel electrolyte. Benefiting from a poly(3, 4‐ethylenedioxythiophene) (PEDOT) buffer layer and a Mn 2+ ‐based neutral electrolyte, the fabricated Zn–MnO2 @PEDOT battery presents a remarkable capacity of 366.6 mA h g −1 and good cycling performance (83.7% after 300 cycles) in aqueous electrolyte. More importantly, when using PVA/ZnCl2 /MnSO4 gel as electrolyte, the as‐fabricated quasi‐solid‐state Zn–MnO2 @PEDOT battery remains highly rechargeable, maintaining more than 77.7% of its initial capacity and nearly 100% Coulombic efficiency after 300 cycles. Moreover, this flexible quasi‐solid‐state Zn–MnO2 battery achieves an admirable energy density of 504.9 W h kg −1 (33.95 mW h cm −3 ), together with a peak power density of 8.6 kW kg −1, substantially higher than most recently reported flexible energy‐storage devices. With the merits of impressive energy density and durability, this highly flexible rechargeable Zn–MnO2 battery opens new opportunities for powering portable and wearable electronics. Abstract : A highly flexible rechargeable quasi‐solid‐state Zn–MnO2 @PEDOT battery is demonstrated for the first time. The battery affords a prominent energy density of 504.9 W h kg −1 (33.95 mW h cm −3 ), substantially outstripping most of the recently reported batteries and supercapacitors. Additionally, benefiting from a protective layer and modified electrolyte, such a Zn–MnO2 @PEDOT battery delivers a good durability of 77.7% after 300 cycles.